TETRAVALENT MANGANESE IN AQUEOUS SOLUTION - Savenko V.S. (My University, 1988)
In view of the absence of experimental studies of the thermodynamic properties of tetravalent manganese compounds in solution, we attempted to evaluate the free energy of formation of the hydroxy complexes of Mn(IV) by comparative calculation methods. Both experiments and calculations indicate that manganese dioxide has a rather high solubility in aqueous solution, i.e., above 50-200 μg Mn/liter at a pH of 6-8, which is much higher than the concentration of manganese in sea water (0.1-2 μg Mn/liter), but is consistent with concentrations found in interstitial waters of pelagic ocean sediments. This means that the direct chemical deposition of manganese dioxide from sea water is impossible and that pelagic ferromaganese nodules thus cannot have been formed in this way. But the data indicate that conditions in the sediments are favorable to the generation of ferromanganese whose growth involves diagenetic processes in a thin surface layer of the sediments.